Implementation of Istishna Akad in Online Sale and Purchase Transactions - Aula Tio Sopa; Olga Mutiara Umi; Mirabai Bhhana (Yayasan Darussalam Bengkulu, 2023)
This study analyzes the use of istishna contracts in online buying and selling transactions. Then the method used in making this journal is a qualitative research method and in collecting data using secondary data, namely by collecting data through websites, journals, and books. In using the istishna contract in online buying and selling transactions, it already follows the provisions or pillars of the istishna contract. The istishna contract can also end based on several things, one of which is the non-fulfillment of formal obligations by the parties involved. Online buying and selling transactions that are growing rapidly, in an Islamic perspective, fall into the category of business or commerce. In Islam, there are rules governing sellers and buyers in buying and selling transactions. This research explores the pillars and conditions for conducting online buying and selling transactions and the implementation of Istishna contracts in online buying and selling transactions. The results of this study determine the sale and purchase transactions in Islam with an istishna contract and what form the transaction takes.